L’analyse HOTS ou des capacités de réflexion de haut niveau du test formatif fait par les professeurs du français aux lycées à Batang - M. Alfin Jaza’; Dwi Astuti (Universitas Negeri Semarang, 2024)
In facing the current era of globalization in the 21st century, a person is required to have various skills to be able to adapt and contribute. Aligned in the curriculum, that assessment is expected to be able to help students have 21st-century skills through international standard questions, namely Higher Order Thinking Skills (HOTS). The purpose of this study is to describe the percentage of formative tests made by French teachers at Senior High Schools in Batang based on HOTS characteristics. The approach used in this study is quantitative descriptive. The object of this study is formative of class XII made by a French teacher at a Senior High School in Batang. The data collection method used is documentation. After data from the formative test was collected, the data was analyzed according to HOTS characteristics. The results showed that 23% of the questions met the HOTS questions and the variety of questions that met the HOTS question criteria was multiple choice.